Blood Rheology and It’s Effect in Various Clinical Conditio - Rahardjo, Theresia Monica; Wargahadibrata, Himendra (Majalah Anestesia dan Critical Care, 2015)
Blood ia a heterogen fluid consists of a suspension of blood cells, erythrocyte, leucocyte, thrombocyte, in a liquid plasma which contains water, proteins, mineral ions, hormones and glucose. Blood rheology is well known has an important rule in circulation. Blood viscosity depend on shear forces and determined by hematocrit, plasma viscocity, blood cells distribution and mechanical properties. Blood rheology can be altered in various pathology proccess like diorder of hematocrit, erytrocute deformability and aggregation. Hematocrit alteration contributed significantly to hemorheology variation and extreme physiologist conditions. Erytrocyte deformability sensitive to local and general homeostasis caused by endogen or exogen factors. Erythrocyte aggregation is determined by plasma protein composition and erythrocyte surface properties like acute phase of inflammation, other factors are in vivo aging, free radical and proteolitic enzymes. Rheology alteration will cause impairment of blood fluidity which is significantly affect tissue perfusion and result in organ function deteriorations, especially if disease processes also disturb vascular properties. This review will reveal blood rheology effect on various pathological conditions, like sepsis, hypertension and diabetes mellitus.